2003
DOI: 10.1111/j.1945-5100.2003.tb00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Ion microprobe U‐Th‐Pb dating of phosphates in martian meteorite ALH 84001

Abstract: Ion microprobe U-Th-Pb dating of phosphates in martian meteorite ALH 84001 Pb age of 3971 ± 860 Ma. These ages are consistent within a 95% confidence limit. This result is in agreement with the previously published Ar-Ar shock age of 4.0 ± 0.1 Ga from maskelynite and other results of 3.8-4.3 Ga but are significantly different from the Sm-Nd age of 4.50 ± 0.13 Ga based on the whole rock and pyroxene. Taking into account recent studies on textural and chemical evidence of phosphate, our result suggests that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…200 ppm (Sano et al, 1999), the concentrations of U in the observed merrillite grains are significantly lower and show smaller variations. The variations of U concentrations observed in individual grains are even smaller than those of grain-to-grain differences reported previously for apatite and merrillite in ALH 84001 (Terada et al, 2003). Although the variation is rather small, the observed distributions of U contents are not random but instead show some trend.…”
Section: Concentrations Of Uraniummentioning
confidence: 45%
See 4 more Smart Citations
“…200 ppm (Sano et al, 1999), the concentrations of U in the observed merrillite grains are significantly lower and show smaller variations. The variations of U concentrations observed in individual grains are even smaller than those of grain-to-grain differences reported previously for apatite and merrillite in ALH 84001 (Terada et al, 2003). Although the variation is rather small, the observed distributions of U contents are not random but instead show some trend.…”
Section: Concentrations Of Uraniummentioning
confidence: 45%
“…Diffusion parameters of U or Pb in merrillite are not well known. However, it might be reasonable to apply those of apatite in this case because previous data of U-Th-Pb analyses of apatite and merrillite plot on the same regression lines (Sano et al, 2000;Terada et al, 2003), which indicates diffusion behaviors of U-Th-Pb system are not significantly different between the two. Therefore, we apply apatite parameters to our results here.…”
Section: Interpretation Of U-pb Agesmentioning
confidence: 99%
See 3 more Smart Citations